Towards sustainable low cost high rise urban housing in Kuala Lmpur, Malaysia - Aminuddin, Asrul (2019)
Sustainability is a multi-dimensional concept when applied to our built environment. Not only does sustainability require that housing developments are designed, developed, constructed and managed in a way which minimises negative impacts on the environment and society as a whole but also the community of which the development is part can only be sustainable if it is a place where people want to live now and in the future.